Kandungan Nitrat dan Fosfat Sedimen serta Keterkaitannya dengan Kerapatan Mangrove di Kawasan Mertasari di Aliran Sungai TPA Suwung Denpasar, Bali - Ni Nyoman Desi Kusuma Dewi; I Gusti Ngurah Putra Dirgayusa; Yulianto Suteja (Fakultas Kelautan dan Perikanan Universitas Udayana, 2017)
Mangrove is a green plants tolerant of salt water, which grows mainly along the sheltered coastal areas, especially along the bay or in estuaries. Final Disposal (TPA) Rubbish Suwung which located in the village Pedungan South Denpasar District is the rubbish dumps originating from the city of Denpasar and Badung. There is a natural mangrove vegetation in the river TPA. Mertsari area which located in the village of Sanur, West Denpasar District is a mangrove planting area and tourism destination on the Mertasari Beach. The purpose of this research are as follows: (1) To identify the content of nitrate and phosphate in mangrove sediments, (2) To determine the density of mangrove in Region Mertasari and TPA Suwung River Flow and (3) To describe the mangrove density is linkage with nitrate and phosphate mangrove sediments. The method used on this research is linear regression. Nitrate and phosphate sediments of mangroves in TPA Suwung River Flow and Region Mertasari range of 0.04 ppm - 79.034 ppm. The average density results of the mangrove tree level, saplings and seedlings in different locations ranged 0.01 ind / m2 - 0.32 ind / m2. The river's flow TPA Suwung produce a simple linear regression calculation of nitrate mangrove sediments density y = -0,002x + 0,288 (R2 ) 10,1 %, and the calculation of the density sedimentary phosphate mangrove produce y = 0,007x + 0,125 (R2) 6,1 %. The results of simple linear regression calculation of nitrate sediments density Mertasari mangrove area is y = -0,002x+ 0,537 R2 = 4,7%, and the calculation of the density sedimentary phosphate mangrove produce y = -0,038x + 0,777 (R2) 63,7 %.